Analysis of precipitation variability over Satluj Basin, Himachal Pradesh, India: 1901–2013 - Nity Tirkey (IWA Publishing, 2021)
Himachal Pradesh is a mountainous state in the Indian Himalayas, which spreads over an area of 55,000 km2. The state has a unique geography, which influences the climatic variability of the state. In the present study, Satluj Basin has been considered as a study area. This basin experiences frequent floods, erratic distribution of rainfall and climatic variabilities, which causes extensive damage over the basin. Precipitation is one of the most crucial meteorological variables which determines the impact of climate change in the Himalayan landmass. For spatial and temporal variation of precipitation, long-term precipitation data of 113 years (1901–2013) was utilized. Further, non-parametric, i.e. Mann–Kendall (MK) and modified Mann–Kendall (MMK) tests, were performed to check possible trends and Sen's slope estimator (SSE) test was used for determining the change in magnitude over the basin at 95% level of significance. The entire analysis was performed on a monthly, annual and seasonal (pre-monsoon, monsoon, post-monsoon and winter) basis. In this study, it was noticed that both positive and negative trends are detected in monthly and seasonal time series. It was also noticed that similar results have been estimated in MK, MMK and Sen's slope estimator tests during 1901–2013.